MEWUJUDKAN KEADILAN SOSIAL MELALUI PENDIDIKAN PANCASILA - Sinaga, Haikal Luthfan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Pancasila education plays a strategic role in the formation of a just and civilized national character. In the context of Indonesian society that still faces various forms of social inequality, Pancasila education can be a tool to strengthen the values ​​of social justice, especially as contained in the fifth principle. This essay aims to examine the contribution of Pancasila education in realizing social justice, analyze the challenges faced in its implementation in educational environments, and offer approaches and strategies that are contextual and relevant to the lives of students. By referring to literature, educational practices, and contemporary social phenomena, this paper emphasizes the importance of revitalizing Pancasila education to be more applicable, participatory, and touch on real life aspects.